2018
DOI: 10.1501/vetfak_0000002820
|View full text |Cite
|
Sign up to set email alerts
|

Besi sığırlarında solunum sistemi virüslerinin seroprevalansı ve persiste BVD virüs enfeksiyonu tespiti

Abstract: Özet: Sığır solunum sistemi enfeksiyonları tüm dünyada besi ve süt sığırı işletmelerindeki en önemli problemlerden birisidir.Bu çalışmada, büyük kapasiteli bir besi sığırı işletmesinde bulunan üç farklı yaş grubundaki (6-8 aylık; 9-11 aylık; 12-15 aylık) hayvanlarda solunum sistemi virüslerinin serolojik dağılımı incelenmiştir. Bu kapsamda örneklenen hayvanlarda, bovine viral diarrhoea virüs (BVDV), bovine herpesvirüs-1 (BHV-1), bovine respiratorik sinsityal virüs (BRSV) ve bovine parainfluenza -3 (PI-3) virüs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…Seroprevalence studies in our country were performed with serum samples from animals that were not vaccinated against BRSV. The seroprevalence (34%-33 of 97 sera) found in the non-vaccinated cattle in the present study was lower than the seropositivity values previously determined in our country [ 47 , 48 , 49 , 50 , 51 , 52 ]. In the present study, BRSV antibodies were detected in 43 samples (66%) out of 65 sera from vaccinated cattle.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Seroprevalence studies in our country were performed with serum samples from animals that were not vaccinated against BRSV. The seroprevalence (34%-33 of 97 sera) found in the non-vaccinated cattle in the present study was lower than the seropositivity values previously determined in our country [ 47 , 48 , 49 , 50 , 51 , 52 ]. In the present study, BRSV antibodies were detected in 43 samples (66%) out of 65 sera from vaccinated cattle.…”
Section: Discussioncontrasting
confidence: 89%
“…The first study reported 46.12% seropositivity in non-vaccinated cattle [ 47 ]. Non-vaccinated cattle sera were analysed in another study in Turkey, which found seropositivity of 44.6% in Central Anatolia [ 48 ], 58.48% in Afyonkarahisar and Usak provinces [ 27 ], 67.3% in Eastern and Southeastern Anatolia [ 49 ], 73% in Marmara Region [ 50 ], 76.38% in Denizli and Burdur provinces [ 51 ], 97.1%in Adiyaman province [ 52 ], and 98.6% in Aydın province [ 51 ]. In neighboring countries, BRSV seroprevalence in non-vaccinated animals was found to be 83.11% in Iraq [ 53 ] and 51.1% [ 54 ] and 89.1% in two studies from Iran [ 55 ].…”
Section: Discussionmentioning
confidence: 99%